Evaluation of the antimicrobial activity of pecan nut [Carya illinoinensis (Wangenh) C. Koch] shell aqueous extract on minimally processed lettuce leaves - CAXAMBÚ,Sabrina (2016)
Abstract Pecan nutshell is a residue from food industry that has potential to be used as biopreservative in foods. The objective of this study was to evaluate the antimicrobial activity of pecan nutshell aqueous extract in vitro and its effectiveness to inhibit spoilage microorganisms on lettuce leaves. The results indicate that the aqueous extract presents inhibitory activity against important foodborne pathogenic bacteria such as Listeria monocytogenes, Salmonella Enteritidis, Staphylococcus aureus, Bacillus cereus, Aeromonas hydrophila and Pseudomonas aeruginosa. Antimicrobial activity was not observed against Corynebacterium fimi, Clostridium perfringens, Escherichia coli, and the phytopathogenic fungi tested. When applied onto lettuce leaves, pecan nutshell extract reduced the counts of mesophilic and psychrotrophic bacteria in 2 and 4 log CFU/g, respectively, during storage of leafy for 5 days at refrigeration temperature (5 °C). The extract was not effective to inhibit yeast on lettuce leaves. Thus, the aqueous extract of pecan shell showed great potential to be used as a natural preservative in foods, acting mainly in the inhibition of spoilage and pathogenic bacteria.